Treatment of symptomatic atrial tachycardia in complex anatomic conditions: use and outcome of ablation in patients after damus-kaye-stansel surgery. (24th May 2021) - Fischer, AJ; Ho, SY; Ernst, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atrial tachycardias (AT) are amongst the most frequent complications in adult patients with congenital heart disease (ACHD). Their incidence mainly depends on age and complexity of underlying defect. AT has a marked impact on morbidity and mortality and is associated with sudden cardiac death particularly in complex ACHD patients. The arrhythmic substrate can be variable from re-entry to multifocal resulting in demanding requirements for electrophysiologic ablation procedures (EP) and thus, relatively high rates of recurrence. Methods and results: Retrospective analysis of ACHD patients with prior Damus-Kaye-Stansel (DKS) surgery treated at one of the largest specialized tertiary centers for ACHD patients worldwide. Analysis focussed on occurrence of AT, respective treatment and outcome of EP. Over a median observation time of 15 years, 13 patients with prior DKS surgery and complex congenital heart defects of different types but uniformly Fontan circulation, were identified (median age 22.0 years (IQR 20.5 – 25.5), 76.9% male, 92.3% NYHA Class I, median systemic ventricular ejection fraction 58.5%, 69.2% extracardiac tunnel). Seven patients (53.8%) presented with symptomatic AT (median cyclic length 440 ms (IQR 360.0 – 517.5)). Of these, six patients underwent EP. Median procedure time was 180.5 min (IQR 160.8 – 274.5), median fluoroscopy time 1.56 min (IQR 0.51 – 4.73) and radiofrequency time 851 sec (265.0 -2005.0). Remote magnetic navigation was used to access ablation site through a retrograde access via the aortic as well as the neo-aortic valve. Three-dimensional image integration aided in mapping and ablation. Throughout the procedure as well as in follow-up visits, no reportable complications were observed. After a mean of 1.5 procedures, all analysed patients stayed complaint-free throughout a median time-interval of 13 months. Conclusion: AT are frequent in complex univentricular situations after Damus-Kaye-Stansel surgery (53.8%). Although more than one procedure (mean 1.5) was necessary to achieve satisfactory results even in experienced hands, EP appears to be an appropriate treatment strategy in this young and otherwise healthy patient cohort. According to our analysis, EP is feasible and safe in centers with knowledge of specific anatomic characteristics of congenital heart disease and when the appropriate technical infrastructure is present. Access to ablation site was performed by remote magnetic navigation in the majority of procedures. The floppy catheter was navigated through the neo-aortic as well as through the aortic valve without observable peri- or postinterventional complications. Mapping with three-dimensional image integration facilitated EP and led to a relatively low radiation exposure with the known benefits for the patient as well as for the healthcare professionals involved in the procedure.